Develop A Wordless Picture Book to Improve Critical Thinking Skills in Elementary School - Marini, Arita; Sari, Yofita; Mufida, Wilda (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2023)
The purpose of this development research is to look at the making of a wordless picture book, to determine the level of validity, practicality, and effectiveness of the development of a wordless picture book. The research method used in this research is Research and Development (R&D), with the ADDIE development model. The validation of this wordless picture book was carried out by 3 experts. The results are 92,5% material expert, 92,5% linguist, and 92,5% media expert. The research subjects were fourth-grade students, totaling 20 students. The product trial phase uses one-to-one and small groups. The results of the research on the development of a wordless picture book that the practicality level of the teacher is 91,6% and the students are 88,6% based on the given instrument. Meanwhile, the effectiveness level of a wordless picture book is that the average post-test value is greater than the pre-test score (79,5 > 30,5). Based on the results of the t-test, tcount (14,41) > ttable (2,09), then the hypothesis (Ha)is accepted. Therefore, a wordless picture book is effectively used in learning.